Entry, Exit, and Diffusion with Learning by Doing - Jovanovic, Boyan; Lach, Saul (American Economic Review, 1989)
Early entry has the advantage of higher revenues per unit of output early on. Late entry has the benefit of learning from the experience of earlier entrants, and hence lower production costs. These advantages are balanced off in a continuous time perfect foresight equilibrium. Competition generates S-shaped diffusion, and staggered entry and exit. A monopolist will innovate less than a competitive industry, but the innovation that he does do, he will do sooner.